Communication—Fe/FeNi3 Embedded in Nitrogen-Doped Carbon Nanotubes as Bifunctional Oxygen Electrocatalysts. Issue 14 (21st October 2020) - Dai, Chengxiang; Fan, Fenghui; Lv, Mengyao; Pan, Longhai; Liang, Shuqin; Wang, Jiacheng; Shen, Hangjia; Thomas, Tiju; Yang, Minghui
Abstract : Both oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) are crucial for metal-air batteries. Achieving a single phase that offers both functionalities is of practical relevance. Here, we report a facile method to couple Fe-Nx moieties and FeNi3 nanoparticles, and embed these in nitrogen-doped carbon nanotubes (Fe/FeNi3 @NC). The Fe/FeNi3 @NC catalyst demonstrates excellent bifunctional performance in 0.10 molar potassium hydroxide. We observe a half-wave potential of 0.83 V for ORR, and a potential of 1.58 V at a current density of 10 mA cm −2 for OER. The oxygen electrode fabricated using Fe/FeNi3 @NC exhibits a peak power density of 143 mW cm −2 for rechargeable Zn-air battery. Over a ∼9 h duration test, the material is also shown to be as stable as the commercial Pt/C + IrO2 in operating conditions.